2006
DOI: 10.1111/j.1365-2958.2006.05292.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rot translation by RNAIII, a key feature of agr function

Abstract: SummaryRNAIII is a 514 nt regulatory RNA that is the effector molecule of the staphylococcal agr quorum-sensing system, regulating a large set of virulence and other accessory genes at the level of transcription. RNAIII was discovered nearly 20 years ago and we long ago hypothesized that it would function by regulating the synthesis or activity of one or more intermediary transcription factors. We have finally confirmed this hypothesis, showing that Staphylococcus aureus RNAIII regulates the synthesis of a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
236
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(253 citation statements)
references
References 28 publications
(37 reference statements)
16
236
1
Order By: Relevance
“…This result was supported by the observation that the 15.6 kDa Rot protein (corresponding to 133 residues) co-eluted with SarA, MgrA and SarR in an affinity pull-down assay from whole-cell lysates with a spa promoter fragment (Oscarsson et al, 2005). In addition, studies by Geisinger et al (2006) with the C-terminal histidine fusion of the rot gene in a multicopy plasmid and immunoblot analysis with antihistidine antibody indicated the production of a functional Rot of 17 kDa in the various isogenic S. aureus strains. The published S. aureus N315 genome reveals at least ten proteins with significant homology to SarA (Kuroda et al, 2001), of which nine have been characterized.…”
Section: Characterization Of the Rot Transcriptssupporting
confidence: 68%
See 3 more Smart Citations
“…This result was supported by the observation that the 15.6 kDa Rot protein (corresponding to 133 residues) co-eluted with SarA, MgrA and SarR in an affinity pull-down assay from whole-cell lysates with a spa promoter fragment (Oscarsson et al, 2005). In addition, studies by Geisinger et al (2006) with the C-terminal histidine fusion of the rot gene in a multicopy plasmid and immunoblot analysis with antihistidine antibody indicated the production of a functional Rot of 17 kDa in the various isogenic S. aureus strains. The published S. aureus N315 genome reveals at least ten proteins with significant homology to SarA (Kuroda et al, 2001), of which nine have been characterized.…”
Section: Characterization Of the Rot Transcriptssupporting
confidence: 68%
“…A diffused pattern of transcripts appeared particularly in the lateexponential and post-exponential phases, probably due to the presence of the multiple transcripts as evidenced in the primer extension experiment. Alternatively, it may have been due to cleavage of the rot transcripts by the base pairing of the agr RNAIII molecule as suggested by Geisinger et al (2006) or the degradation of the rot transcripts at the postexponential phase of growth. In addition, it is consistent with the primer extension results that the sarA gene product acts as a repressor for rot transcription.…”
Section: Analysis Of Rot Transcription In Wild-type Rn6390 and In An mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptional profiling studies indicate that Rot affects the transcription of 168 genes (SaidSalim et al, 2003), many of which reflect an agr minus phenotype. A recent study suggested that the agr RNAIII molecule may interact with rot mRNA to inhibit Rot translation (Geisinger et al, 2006).…”
Section: C Other Sara Homologsmentioning
confidence: 99%